Imaging of Scarce Archaeological Remains Using Microwave Tomographic Depictions of Ground Penetrating Radar Data - Francesco Soldovieri; Erica Utsi; Raffaele Persico; Amir M. Alani (International Journal of Antennas and Propagation)
The Romano-British site of Barcombe in East Sussex, England, has suffered heavy postdepositional attrition through reuse of the building materials for the effects of ploughing. A detailed GPR survey of the site was carried out in 2001, with results, achieved by usual radar data processing, published in 2002. The current paper reexamines the GPR data using microwave tomography approach, based on a linear inverse scattering model, and a 3D visualization that permits to improve the definition of the villa plan and reexamine the possibility of detecting earlier prehistoric remains.